UTILIZATION OF NANOTECHNOLOGY IN VETERINARY MEDICINE - Ketry Moreira Chaves, Lídia; Oliveira Santos, Andreia; Bernardes Rodrigues, Igor; Dias de Oliveira, Michelly; Manaíra Alves Dias, Jordana; Mitiko Yokoy, Mariza; Gomes da Silva, Edson; Alves de Carvalho, Graziele; Maria Serafim Silva, Diovana; Albeirice Du Rocher, Flávia (Journal of Interdisciplinary Debates, 2024)
In veterinary medicine, particularly in diagnostics, drug administration, and reproductive biology, nanotechnology has made significant contributions. By enabling the precise delivery of unstable or insoluble substances, reducing systemic toxicity, and prolonging the action of the active ingredient at the desired site, nanoparticles enhance the effectiveness of treatments. This translates to fewer doses, reduced costs, and less waste from animal-derived products. Furthermore, nanotechnology aids in diagnostics by detecting pathogens and mapping molecular profiles related to diseases. The sensitivity of tests, increased by nanoparticles, allows for more effective detection of contaminants and microbial agents in animal-derived products, which is crucial for food safety. Nanoparticles and nanotubes are also used in reproductive biology to improve fertility, extend sperm longevity, and facilitate semen purification for artificial insemination. Additionally, implanted nanotubes can monitor hormone levels, aiding in the identification of estrus and the selection of breeders. Despite these advancements, it is crucial to monitor the risks and environmental impacts of nanotechnological technologies to ensure their safety and effectiveness in veterinary medicine. The objective of this work is to explore and evaluate current applications of nanotechnology in veterinary medicine, highlighting its benefits, challenges, and potential for future advancements.